THE COMPLEX ORAL REHABILITATION FROM POSSIBILITIES TO REALITY - Ovidiu Stamatin; Monica Andronache; Roxana Vasluianu; Norina Forna (Romanian Dental Association for Education, 2019)
Aim of the study The complex clinical cases require correct and complete, multidisciplinary rehabilitation, which will have as a final result the homogeneous restoration of the functions of the stomatognathic system, which often imposes a clinical and technological challenge. Material and methods A number of 22 patients were treated with cases of partially extended edentation, in which specific and nonspecific treatment stages were approached, from simple to complex, ranging from acquiring hygiene techniques to extensive interventions on the bone support. Results In 72% of patients, bimaxillary prosthetic rehabilitation was possible, but the general health condition conditioned the pro-prosthetic treatment stages, and postextractional complications conditioned the occlusal rehabilitation. Conclusions The approach of partially extended edentulous patients is a challenge due to the age of edentation, comorbidities, case score and which ensures the dynamics of the fine line between purposes and the medical reality of the clinical case.